Financial Performance Analysis Using the Economic Value Added (EVA) Method at PT Akasha Wira International Tbk. For the period 2020-2025 - Besse Zulfa Sya’diyah; Dian Fitri Anasari; Rahmi Dayanti; Qori Nur Hidayah; Rifat Prasetya; Vincensius Aprian Mared; Yossinomita Yossinomita (Jurnal Administrasi Terapan, 2026)
This study aims to evaluate the financial performance of PT Akasha Wira International Tbk during the 2020 to 2025 period using the Economic Value Added (EVA) method. The EVA method was selected because it measures the economic value added generated by the company after accounting for the cost of capital, providing a more comprehensive performance assessment than conventional financial ratios. This research employs a quantitative descriptive approach using secondary data from the Company’s annual financial statements. EVA is calculated by determining Net Operating Profit After Tax (NOPAT), Invested Capital (IC), and Weighted Average Cost of Capital (WACC). The results reflect the Company’s ability, or inability, to generate economic value added for its shareholders during the observation period. These findings are expected to contribute to management’s strategic decision-making and to investors’ assessment of the company’a fundamental performance based on economic value creation. Keywords: Financial Performance, Capital Management, WACC, EVA, PT Akasha Wira International Tbk.